Diabetes mellitus in elderly - Chentli, Farida (Indian J Endocrinol Metab, 2015)
Diabetes mellitus (DM) frequency is a growing problem worldwide, because of long life expectancy and life style modifications. In old age (≥60–65 years old), DM is becoming an alarming public health problem in developed and even in developing countries as for some authors one from two old persons are diabetic or prediabetic and for others 8 from 10 old persons have some dysglycemia. DM complications and co-morbidities are more frequent in old diabetics compared to their young counterparts. The most frequent are cardiovascular diseases due to old age and to precocious atherosclerosis specific to DM and the most bothersome are visual and cognitive impairments, especially Alzheimer disease and other kind of dementia. Alzheimer disease seems to share the same risk factors as DM, which means insulin resistance due to lack of physical activity and eating disorders. Visual and physical handicaps, depression, and memory troubles are a barrier to care for DM treatment. For this, old diabetics are now classified into two main categories as fit and independent old people able to take any available medication, exactly as their young or middle age counterparts, and fragile or frail persons for whom physical activity, healthy diet, and medical treatment should be individualized according to the presence or lack of cognitive impairment and other co-morbidities. In the last category, the fundamental rule is “go slowly and individualize” to avoid interaction with poly medicated elder persons and fatal iatrogenic hypoglycemias in those treated with sulfonylureas or insulin.